Understanding Christian's Perspective on Peace and War - Petrus K. Farneubun (Jurnal Ilmiah Hubungan Internasional, 2013)
Abstract: Problems of peace and war continues to be debated in theological and moral traditions of Christianity.This paper tries to pick two points. First, the Christian view of peace and war. In the Christian view of peace (peace) is indispensable to justice (justice) and include the dimensions (inner peace) or a spiritual dimension(spiritual peace). This understanding is different from a more secular outlook mean peace at the level of exteriordimensions (outer dimension). Secondly, this paper contradict two major traditions in Christianity regarding theplace of Christians in the war and their obligation to participate. The tradition of pacifism which Christians aregenerally held before St . Agustine, argues that Jesus forbade Christians at all involved in the war or arms. Thistradition believes that peace is achieved only through peaceful means. Conversely, Just War tradition that wasdeveloped by St . Augustine considered that Christians are obliged to participate in the war when the purpose ofwar is to bring peace and uphold justice. St.Augustine in two main principles that must be met, namely Jus AdBellum ( Justice of War ) and Jus in Bello ( Justice in War ) .Keywords : Peace, War, Pacifism, Just War, Christians